The role of protein dynamics and thermal fluctuations in regulating cytochrome c/cytochrome c oxidase electron transfer - Álvarez Paggi, Damián Jorge (2014)
In this overview we present recent combined electrochemical, spectroelectrochemical, spectroscopic and computational studies from our group on the electron transfer reactions of cytochrome c and of the primary electron acceptor of cytochrome c oxidase, the CuA site, in biomimetic complexes. Based on these results, we discuss how protein dynamics and thermal fluctuations may impact on protein ET reactions, comment on the possible physiological relevance of these results, and finally propose a regulatory mechanism that may operate in the Cyt/CcO electron transfer reaction in vivo. This article is part of a Special Issue entitled: 18th European Bioenergetic Conference.